Fabrication of helical SiO2@Fe–N doped C nanofibers and their applications as stable lithium ion battery anodes and superior oxygen reduction reaction catalysts. (10th May 2020) - Wang, Haoran; Cai, Wenjun; Wang, Shun; Li, Baozong; Yang, Yonggang; Li, Yi; Wu, Qi-Hui
Abstract: Helical silica nanofibers have been prepared based on a sol-gel transcription approach. After covering a layer of m-phenylenediamine formaldehyde resin and consequent carbonization, SiO2 @Fe–N doped C nanofibers with C content of 33.7 wt% and N content of 3.86 wt% were produced successfully. When applied as the electrode material for lithium-ion batteries (LIBs), they exhibit a high reversible capacity of 1274 mA h g −1 in the 1000th cycle and superior rating capability, implying the possibility as outstanding candidate anode materials for LIBs. Additionally, owing to the doping of Fe2 O3 and N, the nanofibers also exhibit a well-performed oxygen reduction reaction activity, which is comparable to the commercial Pt/C catalyst.